Ayurvedic Management of Asthenozoospermia- A Case Study - Vinayakan, Vidhya; Sreedhar, Asha (International Research Journal of Ayurveda & Yoga, 2022)
Infertility and problems of impaired fecundity have been a concern through ages and is significant clinical problem today. Of all infertility cases, about 40-50% is due to male factor. In this case a couple with complaints of inability to be get a child even after 3 ½ years of unprotected sexual life attended the OPD of Govt. Ayurveda college Thiruvananthapuram. On detailed evaluation, the semen analysis of male partner aged 33 years showed reduced sperm motility, increased liquefaction time and increased viscosity. The patient was assessed based on sexual functional parameters and semen analysis. The semen analysis report showed increased viscosity, liquefaction time above 60 min and active sperm motility 10% and sluggish motile 35%. According to Ayurveda, the patient was diagnosed as having Granthi shukradushti, with investigations showing evidence of Asthenozoospermia. He was treated with sodhana chikitsa (Purification therapy) followed by samana chikitsa (Pacification therapy) for a period of 3 months. The treatment was done as OP level management. Initially Virechana was done with Avipathy churna then Samana oushadhis like Varanadi kasaya, Aswagandarishta, and Phalasarpis were given for a period of 3 months. Virechana with Avipathy churna was repeated on every 2 weeks. The semen analysis was repeated after 3 months and the report showed significant improvement in the semenogram result.